Implementasi Metode AHP dalam Penentuan Penerimaan Bantuan Langsung Tunai (BLT) Berbasis Web - Desi Yanti Kallu Pare; Andreas Ariyanto Rangga; Lidia Lali Momo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
One of the government initiatives of the Sobawawi sub-district is Direct Cash Assistance, or BLT, which aims to lessen the financial strain on the population. Not everyone is eligible for direct cash assistance because it is meant to help low-income families fulfill their basic necessities. The government offers cash support to those who are considered impoverished through the Direct Cash support (BLT) program. This program is intended to help those who struggle to manage their financial situation. In order to help resolve and minimize errors when assessing who was eligible to receive BLT (Direct Cash Assistance) in the Sobawawi district, a decision support system was developed in response to the issues that arose throughout the selection process. The goal of this system is to support decision-making processes that employ the Analytical Hierarchy Process (AHP) technique. The results of both system and manual computations demonstrate how the decision-making system uses the AHP method's notion to determine. Based on the method employed, the system delivers findings that are legitimate and accurate. Ultimately, alternate priority weights based on ranking are determined.